Comparative study of electronic and steric properties of bulky, electron-rich bisphosphinoethane, bis-NHC and phosphino-NHC chelating ligands in analogous rhodium(I) and iridium(I) COD and carbonyl complexes - Brill, Marcel; Marrwitz, Daniela; Rominger, Frank; Hofmann, Peter (Journal of organometallic chemistry, 2015)
The synthesis and characterization of rhodium(I) and iridium(I) COD (1,5-cyclooctadiene) and carbonyl complexes containing small-bite angle and bulky bisphosphine (bis(di-tert-butylphosphino)ethane = dtbpe), bis-NHC (1,1′-di-tert-butyl-3,3′-methylenediimidazolin-2,2′-ylidene = BisNHC) and phosphino-functionalized NHC (3-tert-butyl-1-(di-tert-butylphosphinomethyl)-imidazolin-2-ylidene = NHCP) ligands is described. X-ray diffraction analysis of most compounds made and spectroscopic data permitted a valuable comparison of the characteristic steric and electronic properties of these related ligand classes and also of the “abnormally” bound form of the NHCP ligand (aNHCP). While the dicarbonyl complexes indicated similar overall donating abilities for the BisNHC and NHCP ligands, dtbpe and the aNHCP ligand were shown to be significantly less or more electron donating, respectively. These complexes also allowed the evaluation of the different σ-donating influences of the NHC moiety in comparison to the phosphine moiety within the hybrid NHC-P systems.